Tuberculosis (TB) treatment outcomes in adult TB patients attending a rural HIV cllinic in South Africa (Bushbuckridge). - Mashimbye, Lawrence (My University, 2010)
South Africa is ranked fourth on the list of 22 high-burden TB countries in the world. Intensifying the prevalence of TB in South Africa is the high TB/HIV co-infection rate, with 44% of new TB patients testing positive for HIV. This burden is intense for rural communities due to poverty and return of people with TB/HIV co-infection who previously migrated for employment. In rural South Africa, TB is the leading cause of mortality in HIV-infected persons, but limited information is available about predictors of death. This study measures TB treatment outcomes in Rixile clinic and assesses predictors of TB mortality. Rixile HIV clinic is based in Tintswalo hospital, Acornhoek, Bushbuckridge, Mpumalanga province. This current study uses secondary data collected through a prospective cohort study conducted by PHRU and RADAR from March 2003 to March 2008 on 3 to 6 monthly intervals. Chi-square and logistic regression statistical tests were used to assess predictors of TB Mortality. TB mortality among study participants was 62.5% during the pre-ARV rollout period (March 2003- October 2005), and treatment completion was 31.7%. Some 5.8% participants interrupted treatment during the pre-ARV rollout period as compared to 4.5% during the ARV rollout period (November 2005- March 2008). TB mortality among study participants was 7.5% during ARV rollout and treatment completion increased to 84.4%. Factors associated with TB mortality were age (p=0.006), sex (p=0.017), BMI (p< 0.001), marital status (p=0.004), education (p=0.03), alcoholic beverages consumption (p=0.04), and ARV treatment (p<0.001). However, only age, sex, and ARV treatment were found to predict TB mortality. The proportion of TB treatment completion was higher and TB mortality was lower during ARV roll-out compared to pre-ARV roll-out. Being at the age of 40 to 75 years, not being on ARV treatment and male sex predicts TB mortality in this population. There is a need to expand ARV treatment and intensify TB care services for older people, particularly males living with HIV in this rural community.
MSc (Med), Epidemiology and Biostatistics, Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: TB treatment; treatment outcomes; tuberculosis